2020
DOI: 10.1016/j.vaccine.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of impact of one dose varicella vaccine on the incidence of chickenpox in Argentina

Abstract: Introduction. Varicella, also known as chickenpox is one of the most common immunizable diseases. In 1998, the World Health Organization (WHO) recommended to incorporate this vaccine in the national immunization programs, which Argentina did in 2015. Objectives. To describe the behavior of the varicella time series for the 2005-2017 period, and to evaluate the impact of the vaccine in Argentina. Methodology. An ecological observational study was performed, using the varicella cases reported in the National Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…We also found higher VE of second-dose vaccination, which was in line with reports from the U.S., Europe, and Asia. 33 38 39 40 41 Earlier studies showed a decline in incidence with the introduction of a two-dose program 40 42 or a decreased occurrence of outbreaks, 16 43 but the actual effectiveness compared to the single-dose vaccine group was rarely studied. In this study, the effectiveness of secondary vaccination was estimated with consistency, enabling comparison with the primary-only vaccinated group.…”
Section: Discussionmentioning
confidence: 99%
“…We also found higher VE of second-dose vaccination, which was in line with reports from the U.S., Europe, and Asia. 33 38 39 40 41 Earlier studies showed a decline in incidence with the introduction of a two-dose program 40 42 or a decreased occurrence of outbreaks, 16 43 but the actual effectiveness compared to the single-dose vaccine group was rarely studied. In this study, the effectiveness of secondary vaccination was estimated with consistency, enabling comparison with the primary-only vaccinated group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the consistent and marked seasonality of varicella in Argentina and other Latin American countries in the pre-UVV era [ 15 , 24 , 35 , 36 ]. This seasonality effect was also observed in the current study in the pre-UVV period.…”
Section: Discussionmentioning
confidence: 96%
“…The high socioeconomic impact of varicella in pediatric patients in Argentina during the pre-UVV period has been documented [ 14 ]. Between 1997 and 2012, a varicella incidence ranging from 250 to 450 cases per 100,000 population was reported, and 272 deaths were recorded, of which 60% were in children aged under 10 years [ 15 ]. The estimated costs per pediatric patient for varicella ranged from United States dollar (USD) 340 for outpatients to USD 3109 for inpatients, amounting to an overall annual cost of approximately 40 million dollars in 2015 (2017 USD) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its relevant burden on health care resources, several countries have introduced varicella vaccination into the recommended routine childhood national immunization schedule. To date, there has been evidence showing a substantial decline in the varicella incidence from some countries that have introduced varicella vaccination [37][38][39][40][41], but most countries have no data about the impact of vaccination. Unexpectedly, some populations (ie, Republic of Korea) that have implemented universal varicella vaccination are facing increases in the incidence of the disease, possibly explained by primary or secondary vaccine failure [42].…”
Section: Varicellamentioning
confidence: 99%